A new troglophilic species of Erebonyx (Orthoptera: Grylloidea: Phalangopsidae) from Brazilian caves - Merlo, Rayanne Lays Sant’ana; Castro-Souza, Rodrigo Antônio; de Medeiros Bento, Diego; Ferreira, Rodrigo Lopes (Zootaxa, 2022)
The genus Erebonyx was proposed to accommodate a single troglobitic species from northeastern Brazil. A second cricket belonging to this genus is herein described, but although it was also found in caves, it does not bear any troglomorphic traits, suggesting it is a troglophilic species. The new species differs from the other species on the genus in the phallic sclerites, presence of developed eyes (with ommatidia), pigmented integument, and the presence of stridulatory file on the tegmina. In addition, we present the description of the external morphology, together with the staining and description of tegmina. Finally, we present a brief discussion regarding its habitat, distribution and possible conservation actions for the species.